Effects of reinforcement sensitivity, impulsivity, and working memory on shoot/don't shoot performance in law enforcement officers and civilians under normal and high cognitive load. - Horn, Robert R.; Paletta, Skylar; Sandri Heidner, Gustavo; Lewinski, William J.; Bartel, Lon; Gwon, Daniel; Murray, Nicholas P. (Ergonomics, 2026)
We compared shoot/don't shoot task (SDST) performance in law enforcement officers (LEOs) and non-officers under normal cognitive load, and under higher load induced by processing a complex dispatch message. We also examined the effects of participants' behavioural activation (BAS) and inhibition (BIS) systems, impulsivity, and working memory on SDST performance. Stimuli were videos of shoot and don't shoot variations performed by three actors. Dependent measures were shoot errors, fail-to-shoot errors, response time, and shooting accuracy. Compared to non-officers, LEOs were more accurate and adapted to make fewer fail-to-shoot errors. They were not faster, and did not make fewer shoot errors. Compared to normal cognitive load, under higher load, participants were quicker and more accurate, but made more shoot errors. The higher cognitive load condition revealed effects that were not present under normal load. Participants making more shoot errors had higher BAS, and BIS than those making fewer or no errors. PRACTITIONER SUMMARY: Police training and experience did not facilitate LEOs holding fire in 'don't shoot' situations compared to non-officers. Processing a complex dispatch message during this task also made participants more prone to making shoot errors, and revealed impacts of other factors such as BAS and BIS.